Outcomes of Transradial Versus Transfemoral Access of Percutaneous Coronary Intervention in STEMI: Systematic Review and Updated Meta-analysis. (4th May 2021) - Sattar, Yasar; Majmundar, Monil; Ullah, Waqas; Mamtani, Sahil; Kumar, Ashish; Robinson, Sam; Zghouzi, Mohamed; Mir, Tanveer; Dhamrah, Umaima; Al-Khadra, Yasser; Pacha, Homam Moussa; Darmoch, Fahed; et al.
ABSTRACT: Background: Transradial (TR) percutaneous coronary intervention (PCI) is a preferable PCI route. The complication difference between TR and TF approaches is controversial. Methods: PubMed, Embase, and the Cochrane databases were queried for PCI outcomes of TR TF in STEMI for major cardiac and cerebrovascular events (MACCE), major bleeding, and mortality. The odds ratio (OR) was calculated using the random-effect model. Results: We included 56 studies comprising of 68, 733 patients (TR, n = 26, 179; TF, n = 42, 537). TR-PCI was associated with statistically significant lower odds of MACCE (OR = 0.66, 95% CI: 0.49–0.88, p-value = 0.005), major bleeding (OR = 0.47, 95% CI 0.32–0.68, p-value<0.001), mortality (OR = 0.59, 95% CI 0.43–0.80, p-value<0.001) at in hospital follow-up. TR-PCI was associated with statistically significant lower MACCE (OR = 0.59, 95% CI 0.43–0.80, p-value<0.001), major bleeding (OR = 0.58, 95% CI 0.49–0.68, p-value<0.001), and mortality (OR = 0.61, 95% CI 0.44–0.86, p-value = 0.005) at 30-day follow-up. The same difference was seen at 1-year. Conclusion: TR-PCI was associated with lower odds of MACCE, major bleeding, and mortality during short- and long-term follow-up.